PENGARUH PENAMBAHAN KATALIS BEKAS (SPENT CATALYST) TERHADAP KINERJA CAMPURAN BERASPAL - Leksminingsih Leksminingsih (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
Research on the use of waste materials has been conducted to find out whether they can be useful for road pavements. Claimed that waste materials such as spent catalyst, slag, fly ash, etc. can be directly used in asphalt mixture by certain process. Waste material used in the research was Spent catalyst from Pertamina Balongan, Cirebon. Laboratory and field experiments were performed using AC wearing course, blended with 5% -10% Spent Catalyst. By adding 5% Spent Catalyst exhibits 28.6% higher Marshall stabilities and 22.2% higher Dynamic Stabilities than that of standard mixes. For field experiments 5% spent catalyst was used and the results showed that 31.3% higher Marshall stability, 21.4% higher Dynamic Stability and 26.1% higher Modulus than those of standard mixes. Field experiments were carried out at km 16.428 in Cileunyi Road, Bandung, West Java. After six months, in slow lane and fast lanes were found 21.9% and 47.4% lower rutting depth was 21,9% and 47,4% lower than that of standard pavement in the pavement with spent catalyst than in standard pavement. From the above results, it can be concluded that spent catalyst can be used to increase the asphalt mix performance mainly in increasing Stiffness in pavements Keywords : Spent Catalyst, AC Wearing Specification, Marshall stability, Dynamic stability, Modulus Resilient.